2022
DOI: 10.3390/ma15176101
|View full text |Cite
|
Sign up to set email alerts
|

Application of Cyanobacteria Arthospira platensis for Bioremediation of Erbium-Contaminated Wastewater

Abstract: Erbium belongs to rare earth elements critical for industry, especially nuclear technology. Cyanobacteria Arthospira platensis was used for Er(III) removal from wastewater by applying biosorption and bioaccumulation processes. The influence of pH, Er(III) concentration, contact time and temperature on the biosorption capacity of Arthospira platensis was determined. The optimal conditions for Er(III) removal were defined as pH 3.0, time 15 min and temperature 20 °C, when 30 mg/g of Er(III) were removed. The kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 38 publications
(82 reference statements)
3
14
0
Order By: Relevance
“…In the case of spirulina biomass, a maximum terbium removal of 66% was attained at pH 3.0, when the biomass surface became negatively charged (Figure 1), leading to an enhanced adsorption. The obtained results are in line with other research studying the adsorption of REEs onto spirulina biomass [57]. A further increase in the pH values resulted firstly in the slight decrease in the terbium removal at pH 4.0 (57%), and then, it was significantly reduced and at pH 6.0-7.0 amounted only to 17%.…”
Section: Effect Of Ph Time and Terbium Concentration On Adsorbents' R...supporting
confidence: 91%
“…In the case of spirulina biomass, a maximum terbium removal of 66% was attained at pH 3.0, when the biomass surface became negatively charged (Figure 1), leading to an enhanced adsorption. The obtained results are in line with other research studying the adsorption of REEs onto spirulina biomass [57]. A further increase in the pH values resulted firstly in the slight decrease in the terbium removal at pH 4.0 (57%), and then, it was significantly reduced and at pH 6.0-7.0 amounted only to 17%.…”
Section: Effect Of Ph Time and Terbium Concentration On Adsorbents' R...supporting
confidence: 91%
“…Thus, the removal capacity of spirulina at the temperature range of 20–50 °C was 59%, and that of the yeast biomass was 69%. Previously, it was shown that temperature almost did not affect the rate of Er removal using spirulina biomass [ 47 ], which was on the level of 61–68% at a temperature range of 20–50 °C. The temperature also did not play an essential role in dysprosium removal with the activated carbon obtained from spent coffee waste [ 1 ], and it was at the level of 80%.…”
Section: Resultsmentioning
confidence: 99%
“…The negative value of ΔH° shows that the dysprosium biosorption onto yeast biomass was exothermic in nature, while on spirulina biomass—endothermic. At ΔH° values lower than 40 kJ/adsorption is considered a physical process, while at values in the range of 80–200 kJ/mol is a chemical process [ 47 ]. The ΔS° values were positive for both biosorbents and show the affinity of the adsorbent for the dysprosium ions, indicating an increase in sorbate concentration in the solid–liquid interface [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…At the end of the cultivation cycle, the biomass was separated from the medium by filtration, washed several times with distillated water to remove the remnants of salt, dried at 105 • C, and homogenized. For the characterization of A. platensis using scanning electron microscopy and Fourier-transform infrared spectroscopy, the neutron activation analysis is presented in [24]. The zeta potential of the biomass was measured using Zetasizer Nano ZSP (Malvern).…”
Section: Experiments With Non-living a Platensis Biomassmentioning
confidence: 99%